2021
DOI: 10.3168/jds.2020-19062
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of pathogen-specific intramammary infections in dairy cows

Abstract: Mastitis is one of the most common diseases in dairy cattle, causing severe economic losses to dairy farmers. Mastitis usually occurs due to intramammary infection (IMI) caused by a variety of pathogenic bacteria. Although good progress has been made in understanding genetics of pathogen-specific clinical mastitis, studies involving genetic analysis of pathogen-specific IMI are scarce. The overall objective of this study was, therefore, to assess genetic variation of overall and pathogenspecific IMI in nonclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
4
8
0
Order By: Relevance
“…In our study, the functional features analyses of milk showed that a total of 23 samples with SCC lower than 200,000 cells/ml were positive for Staphylococcus spp . Such result is in line with other studies reporting low SCC levels in primiparous cows and/or positive for non-aureus staphylococci ( 22 , 23 ). However, recent studies have also described less pathogenic Staphylococcus strains, whose virulence factors could induce less severe mastitis or a delayed SCC increase ( 24 , 25 ).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the functional features analyses of milk showed that a total of 23 samples with SCC lower than 200,000 cells/ml were positive for Staphylococcus spp . Such result is in line with other studies reporting low SCC levels in primiparous cows and/or positive for non-aureus staphylococci ( 22 , 23 ). However, recent studies have also described less pathogenic Staphylococcus strains, whose virulence factors could induce less severe mastitis or a delayed SCC increase ( 24 , 25 ).…”
Section: Discussionsupporting
confidence: 93%
“…This resulted in 63 dates of analysis out of the initial 114. Apart from the β-lactamase gene ( blaZ ), which is expressed in staphylococci with penicillin resistance [ 20 ], milk samples were considered contaminated and thus discarded when presenting ≥3 isolated pathogens [ 21 ]. The final data set consisted of (i) 3239 quarter milk samples from 822 cows in 9 herds for STER and (ii) 5464 composite milk samples from the same number of cows in 145 herds for DHI ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Contaminated samples (≥3 pathogens) represented 1.50% of STER samples and 5.80% of DHI samples. 3 Excluded from the frequency calculation due to contamination [21].…”
Section: Presence Of Pathogensmentioning
confidence: 99%
“…Author details 1 College of Traditional Chinese Veterinary Medicine, Hebei Agricultural University, 2596, Le Kai South Street, Baoding 071001, Hebei, China. 2 Hebei Provincial Veterinary Biotechnology Innovation Center, Baoding, China.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Mastitis is defined as an inflammatory reaction caused by infection of mammary gland tissue. Mastitis is one of the most common diseases in dairy cows and is a serious disease [1] that is prevalent worldwide, severely constraining the development of the global dairy industry. This disease reduces milk production, reduces quality, and increases treatment costs [2].…”
Section: Introductionmentioning
confidence: 99%